Fitts' Theorem in Oculomotor Control: Dissociable Movement Times for Amplitude and Width Manipulations. Issue 6 (1st November 2016) - Heath, Matthew; Samani, Ashna; Tremblay, Luc; Elliott, Digby
ABSTRACT: The authors examined whether movement times (MT) for discrete saccades are constant given equivalent index of difficulty (ID) values (i.e., unitary nature of Fitts' theorem). To that end, we contrasted ID/MT relations for saccades equated for ID but differing with respect to their target amplitudes and widths. Results showed that MT increased with increasing ID within amplitude and width conditions; however, the ID/MT slope was markedly steeper in the former condition. Thus, the amplitude condition imposed greater information processing demands than the width condition—a result indicating that the constituent elements of Fitts' theorem are dissociable (i.e., nonunitary). Further, examination of saccade kinematics demonstrated that the optimal MT for a given target amplitude was largely independent of target width.